Neonatal intrahepatocellular lipid. Issue 5 (22nd August 2008) - Thomas, E L; Uthaya, S; Vasu, V; McCarthy, J P; McEwan, P; Hamilton, G; Bell, J D; Modi, N
Abstract : There is increasing evidence that preterm birth is a risk factor for the development of adiposity associated disease, although the pathophysiological basis is unclear. We have previously shown that preterm infants have increased internal abdominal (visceral) adiposity by term. In adults increased internal adiposity is associated with elevated intrahepatocellular lipid (IHCL). We measured IHCL using 1 H NMR spectroscopy in 26 infants (eight healthy preterm-at-term and 18 term-born) and compared values with a reference group of 32 adults. There was no significant difference between adult and term-born IHCL content. In preterm-at-term infants IHCL was significantly elevated when compared with term-born infants and with adults (IHCL CH2 /water median (interquartile range): preterm 1.69 (1.04–3.53), term 0.21 (0–0.54) and adult 0.55 (0.08–1.57).